Identifikasi Mikoriza Vesikular Arbuskular (MVA) dari Rhizosfer Tanaman Cabai (Capsicum annuum L.) dan Tomat (Solanum lycopersicum L.) serta Perbanyakannya Menggunakan Media Zeolit - WIRAWAN, I WAYAN EKA ADI; SUADA, I KETUT; SUSRAMA, I GEDE KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
ABSTRACT Vesicular Arbuscular Mycorrhizae (VAM) Identification of Chilli ( Capsicum a nnu u m L . ) and Tomato ( Solanum l ycopersicum L. ) Rhizosphere and Its Spore Multiplication in Zeolite Media Various attempts have been made to increase the production of chilli and tomato plants by farmers, including by using  inorganic fertilizer application on and on going basis. Considering potential problems that may occured due to inorganic fertilizer use, aplication of  biological fertilizer which one of them is containing v esicular a rbuscular m ycorrhizae (VAM) could be expected to assist the growth of chi l li and tomato in more naturally manner. This study was aim ed to determine genus and species of VAM in chilli and tomato rhizosphere, its colonization in root tissue , and to examine zeolite media compatibility with corn as a symbiont. Based on the results of the study, it was found four species namely Acaulospora fofeata, A. colombiana, A. Laevis , and Glomus ambisporum in chilli and four species in tomato that were identified as A. fofeata, A. colombiana, Scutellospora calospora, and G. ambisporum . Colonization were found in roots of chilli, tomato , and corn indicated by symbiotic structures arbuscules, vesicles, and inner spores. Zeolite media with corn as symbiotic plant is considered suitable for VAM spore propagation. Keywords: rhizospher e, Acaulospora fofeata, zeolite, inner spore